Uji Toksisitas Akut Effluent Pengolahan Lindi TPA Muara Fajar Terhadap Ikan Mas (Cyprinus Carpiol ) Dengan Metode Renewal Test - Novita Faradisha; Shinta Elystia; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The garbage mixed with rain water will produce leachate. Leachate can be pollution if not treated before being discharged into the environment. The leachate treatment are precipitation process, coagulation-flocculation, sedimentation, and cleaning process. However, effluent of TPA Muara Fajar Landfill was above the standard quality of KEP 51-/MENLH/10/1995 about industrial effluent standard. Therefore research on acute toxicity test of effluent leachate from Muara Fajar Landfil to determine LC50 value and TUa (Toxicity Unit area) value by using renewel test method in 96 hours observation. Testing animal used was goldfish (Cyprinus Carpio L). LC50 value was calculated by probit method which utilized the goldfish mortality and the parameters tested was DO, pH, temperature, COD, and sulfide. The value of LC50 of effluent Muara Fajar Landfill was 3,595% and TUa (Toxicity Unit Area) of effluent Muara Fajar Landfill was 27,81. The results showed that value of effluent could make great acute toxicity. Result show the COD and sulfide leachate of characteristics of Muara Fajar landfill affected goldwish mortality. By the higher concentrations and characteristic by the higher goldwish mortality, which means more toxic the leachate was. By the smaller concentration value and characteristics of leachate by the higher LC50 value, which means the toxicity of the leachate was disminished.Keywords : effluent leachate of muara fajar Landfill, LC50 value, renewal test, toxicity.